2013
DOI: 10.1080/10942912.2010.551310
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition, Antioxidant, and Antibacterial Activities of the Essential Oil and Methanol Extracts ofEucalyptus largiflorensF. Muell

Abstract: This study was designed to examine the chemical composition of essential oil and in vitro antioxidant and antimicrobial activity of the essential oil and methanol extracts of Eucalyptus largiflorens F. Muell. The chemical composition of the hydrodistilled essential oil of the leaves of E. largiflorens was analyzed by gas chromatography and gas chromatography/mass spectrometry. The main constituents of the oil were found to be 1,8-cineole (23.1%), cryptone (15.1%), 4-allyloxyimino-2-carene (11.2%), and 4-terpin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 29 publications
(29 reference statements)
1
11
0
1
Order By: Relevance
“…Dev et al (2011) indicated eugenol (61.7%), isopropyl palpitate (11.3%) and 2,3-dihydroxy propyl elaidate (5.1%) as major chemical compounds among O. basilicum oils. Differences in composition of essential oils might have been derived by harvest time, as well as local, climatic and seasonal factors (Rahimi-Nasrabadi et al, 2013). …”
Section: Resultsmentioning
confidence: 99%
“…Dev et al (2011) indicated eugenol (61.7%), isopropyl palpitate (11.3%) and 2,3-dihydroxy propyl elaidate (5.1%) as major chemical compounds among O. basilicum oils. Differences in composition of essential oils might have been derived by harvest time, as well as local, climatic and seasonal factors (Rahimi-Nasrabadi et al, 2013). …”
Section: Resultsmentioning
confidence: 99%
“…Gupta et al [62] found that the main components of C. citratus essential oil were dominated by citral (77.8%), limonene + traces of eucalyptol (4.0%), geraniol (2.7%), 6 methyl-5hepten-2-one (2.4%) and geranyl acetate (1.1%). The differences in the composition of the essential oil might have been derived both from harvest time and local, climatic and seasonal factors, or it may be hypothesized that these samples belong to a different chemotype [63].…”
Section: Discussionmentioning
confidence: 99%
“…Los fenoles totales estuvieron por encima de los reportados por la literatura para otras especies de eucalipto, teniendo en cuenta que las densidades de los aceites esenciales de las especies estudiadas se encuentran entre 0.88-0.91 g/ml. Dezsi et al, (2015) determinaron fenoles totales para el aceite esencial de E. globulus de 235.87±4.38 mg/g; Rahimi-Nasrabadi et al, (2013) para el aceite esencial de E. largiflorens encontraron fenoles totales constituyentes en la subfracción polar de 142.6±0.9 μg/mg, subfracción no polar 68.6±0,4 mg/g y en el aceite esencial de 36,0±0,6 mg/g. En la figura 6 se observa que la mayor capacidad antioxidante al reducir un complejo férrico a su forma ferrosa la presenta la muestra de E. camaldulensis de Chiriguaná.…”
Section: Fig 4: Fenoles Totales Aceites Esenciales De Eucaliptounclassified